Positive electrode active material for lithium secondary battery, method for producing same and lithium secondary battery including same

JP7652891B2Active Publication Date: 2025-03-27LG ENERGY SOLUTION LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2023518309
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-11-10
Filing Date
2021-11-08
Publication Date
2025-03-27
Estimated Expiration
2041-11-08

AI Technical Summary

Benefits of technology

【0031】 本発明の一態様によれば、一次巨大粒子の平均粒径(D50)の成長と共に結晶サイズも成長することで抵抗が向上した二次粒子を含む正極活物質を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007652891000003
    Figure 0007652891000003
  • Figure 0007652891000004
    Figure 0007652891000004
  • Figure 0007652891000005
    Figure 0007652891000005
Patent Text Reader

Abstract

The present invention relates to a cathode active material including at least one secondary particle comprising an aggregate of primary macroparticles, a method for manufacturing the same, and a lithium secondary battery including the same. According to one aspect of the present invention, the surfaces of the secondary particles can be partially coated with cobalt and aluminum to improve electrochemical properties. This provides a nickel-based cathode active material with improved stability at high temperatures and high voltages.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material for a lithium secondary battery, which contains primary large particles, and a method for producing the same.

[0002] This application claims priority to Korean Patent Application No. 10-2020-0149674, filed on November 10, 2020, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]

[0003] In recent years, with the rapid spread of electronic devices using batteries, such as mobile phones, notebook computers, and electric vehicles, the demand for secondary batteries that are small, lightweight, and have relatively high capacity has been rapidly increasing. In particular, lithium secondary batteries are lightweight and have high energy density, and are in the spotlight as a driving power source for portable devices. Therefore, research and development to improve the performance of lithium secondary batteries has been actively conducted.

[0004] A lithium secondary battery generates electrical energy by oxidation and reduction reactions occurring when lithium ions are inserted / deintercalated at the positive and negative electrodes, with an organic or polymer electrolyte filled between the positive and negative electrodes, which are made of active materials capable of intercalating and deintercalating lithium ions.

[0005] Lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2 or LiMn2O4, etc.), lithium iron phosphate compound (LiFePO4), etc. are used as positive electrode active materials for lithium secondary batteries. Among them, lithium cobalt oxide (LiCoO2) is widely used due to its advantages of high operating voltage and excellent capacity characteristics, and is applied as a positive electrode active material for high voltage. However, due to the rising price and unstable supply of cobalt (Co), there is a limit to its large-scale use as a power source in fields such as electric vehicles, and there is a demand for the development of an alternative positive electrode active material. Therefore, nickel-cobalt-manganese-based lithium composite transition metal oxides (hereinafter simply referred to as "NCM-based lithium composite transition metal oxides") in which part of cobalt (Co) is replaced with nickel (Ni) and manganese (Mn) have been developed.

[0006] Meanwhile, the previously developed NCM-based lithium transition metal composite oxide is in the form of secondary particles formed by agglomeration of primary micro particles, and has a large specific surface area and low particle strength. In addition, when an electrode is manufactured using a positive electrode active material containing secondary particles formed by agglomeration of such primary micro particles and then rolled, there is a risk of significant particle cracking, which may result in a large amount of gas generation during cell operation and reduced stability. In particular, in the case of a high-nickel (Ni) NCM-based lithium transition metal composite oxide in which the nickel (Ni) content is increased to ensure high capacity, structural and chemical stability is further reduced and thermal stability is also difficult to ensure.

[0007] To solve these problems, monoliths have been researched and developed. Monoliths are particles that exist independently of the secondary particles and do not appear to have grain boundaries. However, when such monoliths are synthesized, the crystal structure of the particle surface changes from a layered structure to a rock salt structure. The rock salt structure surface, which is a non-conductor, hinders the movement of lithium ions during charging and discharging, thereby shortening the life of the battery. Summary of the Invention [Problem to be solved by the invention]

[0008] The problem to be solved by the present invention is to provide secondary particles based on a new concept.

[0009] The problem to be solved by the present invention is to improve electrochemical properties by partially coating the surfaces of the secondary particles with a cobalt compound and an aluminum compound.

[0010] This provides a nickel-based positive electrode active material with improved stability, particularly at high temperatures and high voltages. [Means for solving the problem]

[0011] An aspect of the present invention provides a positive electrode active material according to the following embodiment.

[0012] The first embodiment is A positive electrode active material for a lithium secondary battery, comprising at least one secondary particle comprising an aggregate of primary macroparticles, The primary macroparticles have an average particle size (D50) of 1.5 μm or more; a portion of a surface of the secondary particles is coated with a cobalt compound and an aluminum compound; The average particle size (D50) of the secondary particles is 3 to 10 μm, The positive electrode active material relates to a positive electrode active material for a lithium secondary battery, which contains a nickel-based lithium transition metal oxide.

[0013] The second embodiment relates to a positive electrode active material for a lithium secondary battery, in which the cobalt compound and the aluminum compound in the first embodiment are coated in a dot shape.

[0014] The third embodiment is the first or second embodiment, wherein the nickel-based lithium transition metal oxide is Li(Ni x Co y M 1-x-yThe present invention relates to a positive electrode active material for a lithium secondary battery, comprising: Mn, Al, Y, Ti, and Zr, and a cathode active material for a lithium secondary battery, the cathode active material comprising Mn, Al, Y, Ti, and Zr.

[0015] A fourth embodiment relates to a positive electrode active material for a lithium secondary battery, in any one of the above-mentioned embodiments, wherein the cobalt compound includes one or more of LiCoO2, Co(OH)2, CoO, Co2O3, Co3O4, CoO(OH), and Co(OCOCH3)2·4H2O.

[0016] The fifth embodiment relates to a positive electrode active material for a lithium secondary battery, in any one of the above-mentioned embodiments, wherein the aluminum compound includes one or more of Al2O3, Al(OH)3, Al(CH3CO2)3, LiAlO2, and Li5AlO4.

[0017] A sixth embodiment relates to a positive electrode active material for a lithium secondary battery, in which the ratio of the average particle size (D50) of the primary giant particles to the average crystal size of the primary giant particles is 2 or more in any one of the above-mentioned embodiments.

[0018] A seventh embodiment relates to a positive electrode active material for a lithium secondary battery, in any one of the above-mentioned embodiments, wherein the primary giant particles have an average crystal size of 130 nm or more.

[0019] The eighth embodiment relates to a positive electrode active material for a lithium secondary battery, in which the ratio of the average particle size (D50) of the secondary particles to the average particle size (D50) of the primary giant particles is 2 to 4 times.

[0020] Another aspect of the present invention provides a positive electrode for a lithium secondary battery according to the following embodiment.

[0021] The ninth embodiment relates to a positive electrode for a lithium secondary battery, comprising the above-mentioned positive electrode active material.

[0022] Yet another aspect of the present invention provides a lithium secondary battery according to the following embodiment.

[0023] A tenth embodiment provides a lithium secondary battery including the above-mentioned positive electrode active material.

[0024] Yet another aspect of the present invention provides a method for preparing a positive electrode active material according to the following embodiment.

[0025] The eleventh embodiment is a method for preparing a positive electrode active material for a lithium secondary battery, (S1) mixing a precursor containing nickel, cobalt and manganese with a hydroxide to prepare a porous nickel-based lithium transition metal hydroxide precursor; (S2) mixing and heat-treating the porous nickel-based lithium transition metal hydroxide precursor with a lithium source material to prepare secondary particles; (S3) mixing the secondary particles with a cobalt compound and an aluminum compound, and then heat treating the mixture; The positive electrode active material is a positive electrode active material for a lithium secondary battery, comprising at least one secondary particle comprising an aggregate of a primary macroparticle, The primary macroparticles have an average particle size (D50) of 1.5 μm or more; A portion of the surface of the secondary particles is coated with cobalt and aluminum, and the average particle size (D50) of the secondary particles is 3 to 10 μm; The positive electrode active material includes a nickel-based lithium transition metal oxide. The present invention relates to a method for producing a positive electrode active material for a lithium secondary battery.

[0026] A twelfth embodiment relates to the method for producing a positive electrode active material, wherein, in the eleventh embodiment, the step (S1) is performed at 35 to 80° C., and the step (S2) is performed at 700 to 1,000° C.

[0027] A thirteenth embodiment relates to a method for producing a positive electrode active material, in any one of the above-mentioned embodiments, wherein the step (S3) is performed at 600 to 750°C.

[0028] A fourteenth embodiment relates to a method for preparing a positive electrode active material, wherein the step (S1) is performed under a pH condition of 8 to 12 in any one of the above-mentioned embodiments.

[0029] The fifteenth embodiment relates to a method for preparing a positive electrode active material, which does not include a separate water washing step between steps (S2) and (S3) in any one of the above-mentioned embodiments.

[0030] A sixteenth embodiment relates to a method for producing a positive electrode active material, wherein the tap density of the porous nickel-based lithium transition metal hydroxide precursor in step (S2) is 1.5 to 2.5 g / cc in any one of the above-mentioned embodiments. Effect of the Invention

[0031] According to one aspect of the present invention, it is possible to provide a positive electrode active material including secondary particles having improved resistance due to the growth of the crystal size together with the growth of the average particle size (D50) of the primary large particles.

[0032] According to one aspect of the present invention, the surfaces of the secondary particles are partially coated with a cobalt compound and an aluminum compound, thereby making it possible to improve electrochemical properties.

[0033] This makes it possible to provide a nickel-based positive electrode active material with improved stability at high temperatures and high voltages.

[0034] The drawings attached to this specification are intended to illustrate preferred embodiments of the present invention and serve to further understand the technical ideas of the present invention as well as the contents of the invention, and therefore the present invention should not be interpreted as being limited to the matters described in the drawings. Meanwhile, the shape, size, scale, or ratio of elements in the drawings attached to this specification may be exaggerated in order to emphasize a clearer description. [Brief description of the drawings]

[0035] [Figure 1a]1 is a SEM photograph of a positive electrode active material according to Comparative Example 1 of the present invention. [Figure 1b] 1 is a SEM photograph of a positive electrode active material according to Comparative Example 2 of the present invention. [Figure 1c] 1 is a SEM photograph of a positive electrode active material according to Comparative Example 3 of the present invention. [Figure 1d] 1 is a SEM photograph of a positive electrode active material according to Example 1 of the present invention. [Figure 1e] 4 is a SEM photograph of a positive electrode active material according to Example 2 of the present invention. [Diagram 2] 1A is a SEM photograph of a positive electrode active material according to Comparative Example 3 of the present invention, and FIG. 1B is a graph showing the amount of cobalt and FIG. [Diagram 3] 1A is a SEM photograph of a positive electrode active material according to Example 1 of the present invention, and FIG. 1B is a graph showing the amount of cobalt and FIG. [Figure 4] 1 is a graph showing high-temperature storage characteristics of an example of the present invention and a comparative example. [Diagram 5] 1 is a graph showing continuous charging characteristics of an example of the present invention and a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0036] Hereinafter, the embodiment of the present invention will be described in detail. Prior to this, the terms and words used in the present specification and claims should not be interpreted as being limited to their ordinary and dictionary meanings, but should be interpreted as being in accordance with the meaning and concept of the technical idea of ​​the present invention, in accordance with the principle that the inventor himself can appropriately define the concept of the term in order to best describe the invention. Therefore, it should be understood that the configurations shown in the embodiments described in this specification are merely the most preferred embodiment of the present invention, and do not represent the entire technical idea of ​​the present invention, and therefore there may be various equivalents and modifications that can be substituted for them at the time of this application.

[0037] Throughout this specification, when a part "comprises" another component, it means that the part may further include the other component, not excluding the other component, unless otherwise specified.

[0038] In the present specification and claims, "comprising a large number of crystal grains" means a crystal consisting of two or more crystal grains having an average crystal size in a specific range. In this case, the crystal size of the crystal grains can be quantitatively analyzed using X-ray diffraction analysis (XRD) using CuKα X-rays (Xrα). Specifically, the average crystal size of the crystal grains can be quantitatively analyzed by placing the produced particles in a holder and analyzing the diffraction pattern produced by irradiating the particles with X-rays.

[0039] In the present specification and claims, D50 may be defined as the particle diameter at 50% of the particle size distribution, and may be measured using a laser diffraction method. For example, the average particle diameter (D50) of the positive electrode active material may be measured by dispersing the particles of the positive electrode active material in a dispersion medium, introducing the particles into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT3000), irradiating the particles with ultrasonic waves of about 28 kHz at an output of 60 W, and then calculating the average particle diameter (D50) corresponding to 50% of the cumulative volume in the measuring device.

[0040] In the present invention, the term "primary particles" refers to particles that have no apparent grain boundaries when observed at a magnification of 5,000 to 20,000 using a scanning electron microscope. In the present invention, the primary particles can be divided into primary fine particles and primary large particles according to the average particle size (D50).

[0041] In the present invention, the "secondary particles" refer to particles formed by agglomeration of the primary particles.

[0042] In the present invention, the term "single particle" refers to a particle that exists independently of the secondary particles and has no apparent grain boundaries, for example, a particle having a particle size of 0.5 μm or more.

[0043] In the present invention, the term "particle" may mean any one or all of a single particle, a secondary particle, and a primary particle.

[0044] <Cathode active material> One aspect of the present invention provides a positive electrode active material having a secondary particle form different from that of the conventional one.

[0045] in particular, 1) A positive electrode active material for a lithium secondary battery comprising at least one secondary particle comprising an aggregate of a primary macroparticle, 2) the primary macroparticles have an average particle size (D50) of 1.5 μm or more; 3) A portion of the surface of the secondary particles is coated with cobalt and aluminum, 4) The average particle size (D50) of the secondary particles is 3 to 10 μm, 5) The present invention provides a positive electrode active material for a lithium secondary battery, the positive electrode active material including a nickel-based lithium transition metal oxide.

[0046] The secondary particles have the above characteristics 1) to 5), and thus it is possible to provide a nickel-based positive electrode active material with improved stability at high temperatures and high voltages.

[0047] The characteristics 1) to 5) of the secondary particles will be described in detail below.

[0048] <Particle morphology and primary macroparticles> In general, the nickel-based lithium transition metal oxide is in the form of secondary particles, which may be in the form of aggregates of primary particles.

[0049] Specifically, dense nickel-based lithium transition metal hydroxide secondary particles prepared by a coprecipitation method are used as a precursor, and the precursor is mixed with a lithium precursor and sintered at a temperature of less than 960° C. to obtain nickel-based lithium transition metal oxide secondary particles. However, when a cathode active material including such conventional secondary particles is applied to a current collector and then rolled, the particles themselves crack, increasing the specific surface area. If the specific surface area increases, a rock salt structure is formed on the surface, resulting in a problem of reduced resistance.

[0050] In order to solve these problems, a positive electrode active material made of single particles has been developed. Specifically, unlike the conventional method of using the dense nickel-based lithium transition metal hydroxide secondary particles as a precursor, a porous precursor is used compared to the conventional precursor, which allows synthesis at a lower sintering temperature for the same nickel content, and a nickel-based lithium transition metal oxide that is not in the form of secondary particles and is made into a single particle can be obtained. However, such single particles have a problem that the crystal structure of the particle surface changes from a layered structure to a rock salt structure during synthesis of the single particles. The surface of the rock salt structure, which is a non-conductor, hinders the movement of lithium ions during charging and discharging, thereby reducing the life of the battery.

[0051] One aspect of the present invention is to solve such problems.

[0052] When a high-density precursor is fired at a high firing temperature as in the past, it is inevitable that not only the average diameter (D50) of the primary particles but also the average particle size (D50) of the secondary particles will increase.

[0053] Meanwhile, the secondary particles according to one embodiment of the present invention are different from the conventional single particle obtaining method in the following points.

[0054] As described above, conventional single particles are formed by simply increasing the primary firing temperature using a conventional precursor for secondary particles. On the other hand, secondary particles according to one embodiment of the present invention use a separate precursor with high porosity. As a result, primary large particles with large diameters can be grown without increasing the firing temperature, while secondary particles grow relatively insufficiently compared to conventional methods.

[0055] As a result, the secondary particles according to one embodiment of the present invention have the same or similar average particle size (D50) as conventional ones, but have a large average diameter (D50) of primary particles. That is, unlike the general form of conventional positive electrode active materials, in which primary particles with small average particle size are aggregated to form secondary particles, the secondary particles according to the present invention are formed by agglomerating primary giant particles that are larger than the primary particles.

[0056] In the present invention, "primary macroparticles" are those having a mean diameter (D50) of 1.5 μm or more.

[0057] In a specific embodiment of the present invention, the primary large particles may have an average particle size of 1.5 μm or more, 2 μm or more, 2.5 μm or more, 3 μm or more, or 3.5 μm or more, and may have an average particle size of 5 μm or less, 4.5 μm or less, or 4 μm or less. If the average particle size of the primary large particles is less than 1.5 μm, it corresponds to conventional secondary particles, and there may be a problem of particle cracking during rolling.

[0058] In the present invention, the "primary giant particles" may have a ratio of average particle diameter (D50) to average crystal size of 3 or more. That is, compared with primary microparticles constituting conventional secondary particles, the primary giant particles are primary particles in which the average particle diameter and average crystal size have grown simultaneously.

[0059] From the viewpoint of cracks, it is advantageous to have a large average particle size while having no grain boundaries in appearance like conventional single particles. Therefore, the inventors focused on growing the average particle size (D50) of the primary particles. In the process, if only the average particle size (D50) of the primary particles is increased by over-firing, a rock salt structure is formed on the surface of the primary particles, which increases the initial resistance. To solve this problem, they found that it is advantageous to grow the average crystal size of the primary particles together to reduce the resistance.

[0060] That is, the primary large particles in the present invention refer to particles that have a large average crystal size as well as a large average particle size, and have no apparent grain boundaries.

[0061] When the average particle size and average crystal size of the primary particles grow simultaneously in this manner, the resistance is lowered and it has the advantage of a longer life compared to conventional single particles, which have a large increase in resistance due to a rock salt structure formed on the surface when fired at high temperatures.

[0062] In this way, compared to conventional single particles, the "secondary particles composed of aggregates of primary large particles" used in one embodiment of the present invention are advantageous in that resistance is reduced due to an increase in the size of the primary particles themselves and a reduction in the formation of rock salt structures.

[0063] At this time, the average crystal size of the primary giant particles can be quantitatively analyzed by X-ray diffraction analysis (XRD) using CuKα X-rays. Specifically, the average crystal size of the primary giant particles can be quantitatively analyzed by placing the produced particles in a holder, irradiating the particles with X-rays, and analyzing the diffraction pattern produced.

[0064] In a specific embodiment of the present invention, the ratio of the average particle diameter (D50) to the average crystal size may be 2 or more, 2.5 or more, 3 or more, and 50 or less, 40 or less, 35 or less.

[0065] Additionally, the average crystallite size of the primary macroparticles can be 130 nm or more, 150 nm or more, 170 nm or more, 200 nm or more, and can be 300 nm or less, 270 nm or less, or 250 nm or less.

[0066] <Secondary particles> The secondary particles according to one embodiment of the present invention have the same or similar average particle size (D50) as conventional ones, but have a large average diameter (D50) of primary particles. That is, unlike the general form of conventional positive electrode active materials, that is, a form in which primary particles having a small average particle size are aggregated to form secondary particles, the secondary particles are provided in the form of agglomeration of primary giant particles that are enlarged primary particles.

[0067] In a specific embodiment of the present invention, the secondary particles may be an agglomeration of 1 to 30 of the primary giant particles. More specifically, the secondary particles may be an agglomeration of 1 or more, 2 or more, 3 or more, or 4 or more of the primary giant particles within the above numerical range, and may be an agglomeration of 30 or less, 25 or less, 20 or less, 15 or less, or 10 or less of the primary giant particles within the above numerical range.

[0068] The secondary particles according to one embodiment of the present invention have an average diameter (D50) of 3 μm to 10 μm, more specifically, 3 μm or more, 3.5 μm or more, 4 μm or more, or 4.5 μm or more, and 10 μm or less, 8 μm or less, or 7 μm or less.

[0069] Generally, regardless of particle morphology, if the composition is the same, the particle size and the average crystal size within the particle increase as the sintering temperature increases. Meanwhile, in the secondary small particles according to one embodiment of the present invention, a porous precursor is used, and primary large particles having a large particle size can be grown without increasing the sintering temperature compared to the conventional method, while the secondary small particles grow relatively insufficiently compared to the conventional method.

[0070] As a result, the secondary particles according to one aspect of the present invention are composed of primary giant particles having an average diameter and an average crystal size larger than those of conventional primary fine particles, while having the same or similar average diameter (D50) as conventional secondary particles.

[0071] In a specific embodiment of the present invention, the ratio of the average particle size (D50) of the secondary particles to the average particle size (D50) of the primary giant particles can be 2 to 4 times.

[0072] At this time, when the secondary particles are rolled, the primary giant particles fall off and the primary giant particles themselves do not crack. At this time, the rolling condition can be 9 tons (ton).

[0073] The secondary particles contain a nickel-based lithium transition metal oxide.

[0074] Specifically, the nickel-based lithium transition metal oxide contains Li(Ni x Co y M 1-x-y )O2 (M is any one selected from Mn, Al, Y, Ti, Zr, etc. or two or more of these elements).

[0075] In the above formula, x and y represent the molar ratios of the respective elements in the nickel-based lithium transition metal oxide.

[0076] At this time, 0 < x < 1, 0 < y ≤ 0.35, and 0 < x + y ≤ 1 can be satisfied.

[0077] For example, x = 0.8 and y = 0.1 can be satisfied.

[0078] For example, the nickel-based lithium transition metal oxide is LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, and LiNi0.5 Co 0.3 Mn 0.2 It may be selected from the group consisting of O2.

[0079] Nickel (Ni) is an element that contributes to the high potential and high capacity of the secondary battery, and the amount corresponding to x may be included in an amount of 0 < x < 1. If the x value is 0, the charge-discharge capacity characteristics may deteriorate. If the x value exceeds 1, there is a risk of deterioration of the structure and thermal stability of the active material, and thereby deterioration of the life characteristics. Considering the effects of high potential and high capacity by controlling the nickel content, the nickel may be included in an amount of more specifically 0.5 ≦ x < 1, and even more specifically 0.5 ≦ x ≦ 0.8.

[0080] Cobalt (Co) is an element that contributes to the improvement of the charge-discharge cycle characteristics of the active material, and the amount corresponding to y may be included in an amount of 0 < y ≦ 0.35. If y is 0, there is a risk of charge-discharge capacity reduction due to deterioration of structural stability and lithium ion conductivity. If y exceeds 0.35, the driving voltage of the positive electrode active material becomes high, and there is a risk of charge-discharge capacity reduction under a given upper limit voltage. Considering the effect of improving the cycle characteristics of the active material by controlling the cobalt content, the cobalt may be included in an amount of more specifically 0.1 ≦ y < 0.35, and even more specifically 0.1 ≦ y ≦ 0.3.

[0081] On the other hand, in the present invention, the secondary particles are those in which a part of the surface of the particles is coated with a cobalt compound and an aluminum compound.

[0082] For example, the cobalt compound may be any one or more of LiCoO2, Co(OH)2, CoO, Co2O3, Co3O4, CoO(OH), and Co(OCOCH3)2·4H2O.

[0083] For example, the aluminum compound may be any one or more of Al2O3, Al(OH)3, Al(CH3CO2)3, LiAlO2, and Li5AlO4.

[0084] By simultaneously containing a cobalt compound and an aluminum compound in this way, stability at high temperatures and high voltages can be improved.

[0085] If the coating is performed only with a cobalt compound, there is a possibility that the high temperature / high voltage stability will decrease, and if the coating is performed only with an aluminum compound, there is a possibility that the resistance will still be higher than desired.

[0086] Meanwhile, the cobalt compound and the aluminum compound are coated only on a part of the surface of the secondary particles, for example, in the form of dots. If the cobalt compound and the aluminum compound are coated on the entire surface of the secondary particles, there may be a problem that the resistance is still higher than desired.

[0087] <Method of manufacturing positive electrode active material> The positive electrode active material according to an embodiment of the present invention may be prepared by the following method, but is not limited thereto.

[0088] Specifically, the method includes the steps of: (S1) mixing a precursor containing nickel, cobalt, and manganese with a hydroxide to prepare a porous nickel-based lithium transition metal hydroxide precursor; (S2) mixing and heat-treating the porous nickel-based lithium transition metal hydroxide precursor with a lithium source material to prepare secondary particles; (S3) mixing the secondary particles with a cobalt compound and an aluminum compound, and then heat treating the mixture; The positive electrode active material is a positive electrode active material for a lithium secondary battery, comprising at least one secondary particle comprising an aggregate of a primary macroparticle, The primary macroparticles have an average particle size (D50) of 1.5 μm or more; A portion of the surface of the secondary particles is coated with cobalt and aluminum, and the average particle size (D50) of the secondary particles is 3 to 10 μm, The positive electrode active material contains a nickel-based lithium transition metal oxide, and the method relates to a method for producing a positive electrode active material for a lithium secondary battery.

[0089] The method for preparing the positive electrode active material will now be described step by step.

[0090] First, a positive electrode active material precursor containing nickel (Ni), cobalt (Co) and manganese (Mn) is prepared.

[0091] In this case, the precursor for preparing the positive electrode active material may be a commercially available positive electrode active material precursor or may be prepared by a method for preparing a positive electrode active material precursor known in the art. For example, the precursor may have a tap density of 1.5 to 2.5 g / cc.

[0092] For example, the precursor may be prepared by adding an ammonium cation-containing chelating agent and a basic compound to a transition metal solution containing a nickel-containing source material, a cobalt-containing source material, and a manganese-containing source material, and then subjecting the mixture to a coprecipitation reaction.

[0093] The nickel-containing source material may be, for example, a nickel-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and specifically may be, but is not limited to, Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, fatty acid nickel salts, nickel halides, or combinations thereof.

[0094] The cobalt-containing source material may be a cobalt-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and may be, but is not limited to, Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, CoSO4, Co(SO4)2·7H2O, or a combination thereof.

[0095] The manganese-containing source material may be, for example, manganese-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, oxyhydroxide, or a combination thereof, specifically, manganese oxide such as Mn2O3, MnO2, Mn3O4, etc.; manganese salt such as MnCO3, Mn(NO3)2, MnSO4, manganese acetate, manganese dicarboxylate, manganese citrate, and manganese fatty acid salt; manganese oxyhydroxide, manganese chloride, or a combination thereof, but is not limited thereto.

[0096] The transition metal solution may be prepared by adding a nickel-containing raw material, a cobalt-containing raw material, and a manganese-containing raw material to a solvent, specifically, water or a mixed solvent of an organic solvent (e.g., alcohol, etc.) that is uniformly miscible with water, or may be prepared by mixing an aqueous solution of the nickel-containing raw material, an aqueous solution of the cobalt-containing raw material, and the manganese-containing raw material.

[0097] The ammonium cation-containing chelating agent may be, for example, NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, (NH4)2CO3, or a combination thereof, but is not limited thereto. Meanwhile, the ammonium cation-containing chelating agent may be used in the form of an aqueous solution, and the solvent used in this case may be water or a mixture of water and an organic solvent (specifically, alcohol, etc.) that is uniformly miscible with water.

[0098] The basic compound may be a hydroxide of an alkali metal or an alkaline earth metal, such as NaOH, KOH, or Ca(OH)2, a hydrate thereof, or a combination thereof. The basic compound may also be used in the form of an aqueous solution, and the solvent used in this case may be water or a mixture of water and an organic solvent (specifically, an alcohol, etc.) that is uniformly miscible with water.

[0099] The basic compound is added to adjust the pH of the reaction solution, and may be added in an amount such that the pH of the metal solution becomes 8 to 12.

[0100] Next, a porous nickel-based lithium transition metal hydroxide precursor is prepared by mixing a precursor containing nickel, cobalt and manganese with a hydroxide.

[0101] In this case, the coprecipitation reaction can be carried out in an inert atmosphere such as nitrogen or argon at a temperature of 35°C to 80°C.

[0102] This allows a porous nickel-based lithium transition metal hydroxide precursor to be produced by mixing a precursor containing nickel, cobalt and manganese with a hydroxide (S1).

[0103] Through the above process, nickel-cobalt-manganese hydroxide particles are produced and precipitated in the reaction solution. By adjusting the concentrations of the nickel-containing raw material, the cobalt-containing raw material, and the manganese-containing raw material, a precursor having a nickel (Ni) content of 60 mol% or more in the total metal content can be produced. The precipitated nickel-cobalt-manganese hydroxide particles can be separated and dried by a conventional method to obtain a nickel-cobalt-manganese precursor. The precursor can be secondary particles formed by agglomeration of primary particles.

[0104] Thereafter, the precursor and the lithium source material are mixed and heat-treated (primary firing) (S2).

[0105] The lithium source material may be a lithium-containing sulfate, nitrate, acetate, carbonate, oxalate, citrate, halide, hydroxide, or oxyhydroxide, and is not particularly limited as long as it is soluble in water. Specifically, the lithium source material may be Li2CO3, LiNO3, LiNO2, LiOH, LiOH·H2O, LiH, LiF, LiCl, LiBr, LiI, CH3COOLi, Li2O, Li2SO4, CH3COOLi, or Li3C6H5O7, and any one or a mixture of two or more of these may be used.

[0106] In the case of a high-nickel (high-Ni) NCM-based lithium transition metal composite oxide having a nickel (Ni) content of 60 mol % or more, the primary firing may be performed at 700 to 1,000° C., more preferably 780 to 980° C., and even more preferably 780 to 900° C. The primary firing may be performed in an air or oxygen atmosphere for 15 to 35 hours.

[0107] After the primary firing, the cobalt compound and the aluminum compound are mixed together, and then an additional heat treatment (secondary firing) is performed (S3).

[0108] In the case of a high-nickel (high-Ni) NCM-based lithium transition metal composite oxide having a nickel (Ni) content of 60 mol % or more, the secondary firing may be performed at 600 to 750° C., more preferably 630 to 730° C., and even more preferably 600 to 700° C. The secondary firing may be performed in an air or oxygen atmosphere for 10 to 24 hours.

[0109] Meanwhile, the method is characterized in that a separate washing process is not included between the steps (S2) and (S3). In this case, the total amount of lithium remaining in the particles after the primary sintering may be 0.5 to 1.5 wt% based on the total weight of the positive electrode active material. In the past, a process of washing the lithium by-products present on the surface of the positive electrode active material with water was performed. This is because, when the lithium by-products are present, side reactions with the electrolyte occur when the material is applied to a battery, and the amount of gas generated during high-temperature storage increases. Meanwhile, in the manufacturing method according to one embodiment of the present invention, a separate washing process is not performed. As a result, the lithium by-products are present on the surface of the particles, and when the amount of the lithium by-products is 0.5 to 1.5 wt% based on the total weight of the positive electrode active material, a positive electrode active material having secondary particle aggregates including primary giant particles according to one embodiment of the present invention can be manufactured.

[0110] <Positive electrodes and lithium secondary batteries> According to another aspect of the present invention, there is provided a positive electrode for a lithium secondary battery and a lithium secondary battery, each of which includes the positive electrode active material.

[0111] Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.

[0112] In the positive electrode, the positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. may be used. In addition, the positive electrode current collector may usually have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the positive electrode current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0113] The positive electrode active material layer may contain a conductive material and a binder in addition to the positive electrode active material described above.

[0114] In this case, the conductive material is used to impart conductivity to the electrode, and can be used without any particular restrictions as long as it does not cause chemical changes in the battery that is constructed and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and one or more of these may be used alone or in combination. The conductive material may usually be contained in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer.

[0115] The binder also serves to improve the adhesion between the positive electrode active material particles and between the positive electrode active material and the positive electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer.

[0116] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material described above. Specifically, the positive electrode may be manufactured by coating a composition for forming a positive electrode active material layer, which includes the positive electrode active material and, optionally, a binder and a conductive material, on a positive electrode current collector, followed by drying and rolling. In this case, the types and contents of the positive electrode active material, binder, and conductive material are as described above.

[0117] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, etc., and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, taking into consideration the coating thickness of the slurry and the manufacturing yield, and to provide a viscosity that allows excellent thickness uniformity to be achieved when the slurry is applied to manufacture a positive electrode.

[0118] Alternatively, the positive electrode may be manufactured by casting the composition for forming a positive electrode active material layer on a separate support, peeling the composition from the support, and laminating the resulting film on a positive electrode current collector.

[0119] According to yet another aspect of the present invention, there is provided an electrochemical device including the positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0120] The lithium secondary battery may further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0121] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0122] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of typically 3 to 500 μm, and may have fine irregularities formed on the surface of the current collector to enhance the binding force of the negative electrode active material, as in the case of the positive electrode current collector. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0123] The negative electrode active material layer may include a negative electrode active material and, optionally, a binder and a conductive material, and may be manufactured, for example, by coating a negative electrode forming composition including a negative electrode active material and, optionally, a binder and a conductive material on a negative electrode current collector and drying the composition, or by casting the negative electrode forming composition on a separate support and then peeling the composition from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0124] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β (0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a thin film of metallic lithium may be used as the negative electrode active material. In addition, low-crystalline carbon and high-crystalline carbon may be used as the carbon material. Representative examples of low-crystalline carbon include soft carbon and hard carbon, and representative examples of high-crystalline carbon include amorphous, plate-like, scaly, spherical, or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, mesocarbon microbeads, mesophase pitches, and high-temperature calcined carbon such as petroleum or coal-based coke.

[0125] Additionally, the binder and conductive material are the same as those described above for the positive electrode.

[0126] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator generally used in lithium secondary batteries may be used without any particular limitation. In particular, a separator having low resistance to ion movement of the electrolyte and excellent electrolyte impregnation ability is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric material may be used to ensure heat resistance or mechanical strength, and may be selectively used in a single layer or multilayer structure.

[0127] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these.

[0128] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0129] The organic solvent may be any suitable one that can act as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, examples of the organic solvent that can be used include ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; ether solvents such as dibutyl ether and tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC); alcohol solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (R is a C2 to C20 linear, branched, or cyclic hydrocarbon group that may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolanes. Among them, carbonate-based solvents are preferable, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having a high dielectric constant capable of improving the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, etc.) is more preferable. In this case, it is preferable to mix the cyclic carbonate and the linear carbonate in a volume ratio of about 1:1 to about 1:9 for excellent electrolyte performance.

[0130] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in lithium secondary batteries. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt may be within a range of 0.1 to 2.0M. If the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore exhibits excellent electrolyte performance and allows lithium ions to move effectively.

[0131] In addition to the electrolyte components described above, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving battery life characteristics, suppressing a decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5 wt % based on the total weight of the electrolyte.

[0132] A lithium secondary battery containing the positive electrode active material according to the present invention is useful in portable devices such as mobile phones, notebook computers, and digital cameras, and in the field of electric vehicles such as hybrid electric vehicles (HEVs).

[0133] According to yet another aspect of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.

[0134] The battery module or battery pack may be used as a power source for one or more medium to large devices including power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles, and plug-in hybrid electric vehicles (PHEVs); or power storage systems.

[0135] The present invention will now be described in detail with reference to exemplary embodiments so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and is not limited to the exemplary embodiments described below.

[0136] <Comparative Example 1> A coprecipitation reactor (volume 20L) was filled with 4L of distilled water and maintained at 50°C. A 3.2mol / L transition metal solution containing NiSO4, CoSO4, and MnSO4 mixed to give a nickel:cobalt:manganese molar ratio of 0.8:0.1:0.1, and a 28wt% aqueous ammonia solution were continuously fed into the reactor at 300mL / hr and 42mL / hr, respectively. The mixture was stirred at an impeller speed of 400rpm, and a 40wt% sodium hydroxide solution was added to maintain the pH at 9. The mixture was co-precipitated for 10 hours to form precursor particles. The precursor particles were separated, washed, and then dried in an oven at 130°C to produce a precursor.

[0137] Ni synthesized by coprecipitation reaction 0.8 Co 0.1 Mn 0.1 The (OH)2 precursor was mixed with LiOH so that the Li / Me(Ni,Co,Mn) molar ratio was 1.05, and then heat-treated in an oxygen atmosphere at 850°C for 10 hours to obtain LiNi 0.8 Co 0.1 Mn 0.1 A positive electrode active material containing O2 nickel-based lithium transition metal oxide secondary particles was produced.

[0138] <Comparative Example 2> The secondary particles produced in Comparative Example 1 were coated with cobalt using a dry process. Specifically, the secondary particles were produced in the following manner.

[0139] Co(OH)2 and LiNi in Comparative Example 1 0.8 Co 0.1 Mn 0.1 O2 and Co(OH)2 / LiNi 0.8 Co 0.1 Mn 0.1 After mixing under dry conditions so that the O2 weight ratio was 0.1 wt%, the mixture was heat-treated at 700°C in an oxygen atmosphere for 10 hours to obtain cobalt-coated LiNi 0.8 Co 0.1 Mn 0.1 O2 positive electrode active material was produced.

[0140] <Comparative Example 3> The secondary particles produced in Comparative Example 1 were simultaneously coated with cobalt and aluminum at 800° C. using a dry process. Specifically, the secondary particles were produced in the following manner.

[0141] Co(OH)2 and Al2O3 and LiNi in Comparative Example 1 0.8 Co 0.1 Mn 0.1 O2 and Co(OH)2, Al2O3 / LiNi 0.8 Co 0.1 Mn 0.1 After mixing under dry conditions so that the O2 weight ratio was 0.1 wt%, the mixture was heat-treated at 800°C in an oxygen atmosphere for 10 hours to obtain LiNi with a cobalt + aluminum coating. 0.8 Co 0.1 Mn 0.1 O2 positive electrode active material was produced.

[0142] <Example 1> The secondary particles produced in Comparative Example 1 were simultaneously coated with cobalt and aluminum at 700° C. using a dry process. Specifically, the coating was produced in the following manner.

[0143] Co(OH)2 and Al2O3 and LiNi in Comparative Example 1 0.8 Co 0.1 Mn 0.1 O2 and Co(OH)2, Al2O3 / LiNi 0.8 Co 0.1 Mn 0.1After mixing under dry conditions so that the O2 weight ratio was 0.1 wt%, the mixture was heat-treated at 700°C in an oxygen atmosphere for 10 hours to obtain LiNi with a cobalt + aluminum coating. 0.8 Co 0.1 Mn 0.1 O2 positive electrode active material was produced.

[0144] <Example 2> Ni synthesized by coprecipitation reaction in Comparative Example 1 0.8 Co 0.1 Mn 0.1 The (OH)2 precursor was mixed with LiOH so that the Li / Me(Ni,Co,Mn) molar ratio was 1.05, and then heat-treated in an oxygen atmosphere at 880°C for 10 hours to produce LiNi 0.8 Co 0.1 Mn 0.1 A positive electrode active material containing O2 nickel-based lithium transition metal oxide secondary particles was produced.

[0145] The produced secondary particles were simultaneously coated with cobalt and aluminum at 700° C. using the same dry process as in Example 1.

[0146] [Table 1]

[0147] [Experimental Example 1: Observation of Positive Electrode Active Material] Photographs of the positive electrode active materials prepared in Comparative Examples 1 to 3 and Examples 1 and 2 observed under a scanning electron microscope (SEM) are shown in FIGS. 1a to 1e, respectively.

[0148] [Experimental Example 2: Average particle size] D50 may be defined as the particle size at 50% of the particle size distribution, and was measured using a laser diffraction method.

[0149] [Experimental Example 3: Measurement of Capacity Retention Rate] The lithium secondary battery half-cells prepared as described below using the positive electrode active materials prepared in Example 1 and Comparative Examples 1 to 3 were charged at 0.5 C to 4.25 V in CC (constant current)-CV (constant voltage) mode at 45° C., and discharged at a constant current of 1.0 C to 2.5 V, and then charged and discharged 50 times to measure the capacity retention rate and evaluate the life characteristics. The results are shown in Table 1.

[0150] Specifically, the lithium secondary battery half-cell was manufactured as follows.

[0151] The positive electrode active materials prepared in Example 1 and Comparative Example 1, the carbon black conductive material, and the PVDF binder were mixed in a weight ratio of 96:2:2 in N-methylpyrrolidone solvent to prepare a positive electrode mixture, which was then coated on one side of an aluminum current collector, dried at 100°C, and rolled to prepare a positive electrode.

[0152] Lithium metal was used as the negative electrode.

[0153] A porous polyethylene separator was interposed between the positive and negative electrodes to prepare an electrode assembly, and the electrode assembly was placed inside a case, and an electrolyte was injected into the case to prepare a lithium secondary battery. The electrolyte was prepared by dissolving 1.0M lithium hexafluorophosphate (LiPF6) in an organic solvent consisting of ethylene carbonate / ethyl methyl carbonate / diethyl carbonate (EC / EMC / DEC mixed volume ratio = 3 / 4 / 3).

[0154] [Experimental Example 4: Crystal size of primary particles] The samples were measured using a Bruker Endeavor (CuKα, λ = 1.54 Å) equipped with a LynxEye XE-T position sensitive detector, with FDS 0.5°, 2θ 15° to 90° range, step size 0.02°, and a total scan time of 20 min.

[0155] The measured data were subjected to Rietveld refinement, taking into account the charge (+3 for metals at transition metal sites, +2 for Ni at Li sites) and cation mixing from each site. For crystal size analysis, instrumental broadening was considered using the Fundamental Parameter Approach (FPA) implemented in the TOPAS program manufactured by Bruker, and the entire peak in the measurement range was used for fitting. Peak morphology was fitted using only the Lorenzian contribution in the First Principle (FP) of the peak types available in TOPAS, and strain was not considered. The crystal size results are shown in Table 1.

[0156] [Experimental Example 5: Continuous charging characteristics] After charging to a high voltage (4.6V) at a constant current of 0.2C, the constant voltage was applied and the current (leakage current) was measured. The time it took for the leakage current to reach the original 0.2C current value was measured. The results are shown in Table 2.

[0157] [Table 2]

Claims

1. A positive electrode active material for a lithium secondary battery comprising at least one secondary particle comprising an aggregate of a primary macroparticle, The primary macroparticles have an average particle size (D50) of 1.5 μm or more; a portion of a surface of the secondary particles is coated with a cobalt compound and an aluminum compound; The average particle size (D50) of the secondary particles is 3 to 10 μm, The positive electrode active material for a lithium secondary battery contains a nickel-based lithium transition metal oxide.

2. The positive electrode active material for a lithium secondary battery according to claim 1 , wherein the cobalt compound and the aluminum compound are coated in a dot shape.

3. The nickel-based lithium transition metal oxide is Li(Ni x Co y M 1-x-y ) O 2 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein M is any one or more elements selected from Mn, Al, Y, Ti, and Zr, and 0<x<1, 0<y≦0.35, and 0<x+y≦1.

4. The cobalt compound is LiCoO 2 , Co(OH) 2 , CoO, Co 2 O 3 , Co 3 O 4 , CoO(OH), and Co(OCOCH 3 ) 2 ・4H 2 The positive electrode active material for a lithium secondary battery according to claim 1 , further comprising at least one of O.

5. The aluminum compound is Al 2 O 3 , Al(OH) 3 , Al(CH 3 CO 2 ) 3 , LiAlO 2 , and Li 5 AlO 4 The positive electrode active material for a lithium secondary battery according to claim 1 , comprising at least one of the following:

6. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein a ratio of an average particle size (D50) of the primary large particles to an average crystal size of the primary large particles is 2 or more.

7. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the primary macroparticles have an average crystal size of 130 nm or more.

8. 2. The positive electrode active material for lithium secondary batteries according to claim 1, wherein the ratio of the average particle size (D50) of the secondary particles to the average particle size (D50) of the primary large particles is 2 to 4 times.

9. A positive electrode for a lithium secondary battery comprising the positive electrode active material for a lithium secondary battery according to claim 1.

10. A lithium secondary battery comprising the positive electrode active material for lithium secondary batteries according to claim 1.

11. A method for producing a positive electrode active material for a lithium secondary battery, comprising: (S1) adding a basic compound to a transition metal solution containing a nickel-containing source material, a cobalt-containing source material, and a manganese-containing source material, and co-precipitating the solution to prepare a porous precursor; (S2) mixing and heat-treating the porous precursor and a lithium source material to prepare secondary particles; (S3) mixing the secondary particles with a cobalt compound and an aluminum compound, and then heat treating the mixture; The positive electrode active material for a lithium secondary battery includes at least one secondary particle including an aggregate of a primary large particle, The primary macroparticles have an average particle size (D50) of 1.5 μm or more; a part of the surface of the secondary particles is coated with a cobalt compound and an aluminum compound, and the average particle size (D50) of the secondary particles is 3 to 10 μm; The positive electrode active material for a lithium secondary battery includes a nickel-based lithium transition metal oxide.

12. The step (S1) is carried out at 35 to 80° C. The method of claim 11, wherein the step (S2) is performed at 700 to 1,000° C.

13. The method of claim 11, wherein the step (S3) is performed at 600 to 750°C.

14. The method of claim 11, wherein the step (S1) is performed under a pH condition of 8 to 12.

15. The method for preparing a positive active material according to claim 11, wherein a separate water washing step is not included between the step (S2) and the step (S3).

16. The method for producing a positive electrode active material according to claim 11, wherein the tap density of the porous precursor in the step (S2) is 1.5 to 2.5 g / cc.

Citation Information

Patent Citations

  • Co-Al active material-coated nickel-cobalt-manganese ternary layered positive electrode material and preparation method thereof

    CN110224124A

  • Cathode active material, method of producing the same, and cathode and lithium secondary battery employing the same

    JP2015018803A

  • Cathode active material for nonaqueous electrolyte secondary cell and production method therefor and nonaqueous electrolyte secondary cell

    JP2016222483A

  • Composite cathode active material, method of preparing the same, and cathode and lithium battery including the composite cathode active material

    JP2019046795A

  • Positive electrode active material for lithium secondary battery and lithium secondary battery including the same

    JP2020077611A